Pemahaman Teks Keagamaan: Konsep ‘Amm dan Khash dalam Interpretasi Al-Qur’an - Ahmed Hafiz Al Fikri; Sutrisno Hadi; Muhammad Arpah Nurhayat (Jurnal Teologi Islam, 2025)
This study aims to deeply dissect the concepts of ‘Amm (general) and Khash (specific) in the disciplines of Usul Fiqh and the study of Qur'anic exegesis. These two concepts are fundamental methodological instruments that determine the accuracy in interpreting sacred texts, especially in establishing Islamic law. This study uses a qualitative approach, content analysis method of primary literature on Usul Fiqh and exegesis. The results of the study indicate that the understanding of ‘Amm and Khash is not merely a linguistic distinction, but a complex epistemological framework. The concept of ‘Amm is defined as a word that encompasses all units that are appropriate for it without limits, with various forms and linguistic indicators. Meanwhile, Khash is a word that is limited to certain units. The interaction between the two, such as the process of takhshish (specification) of a general text, is key to understanding the seemingly contradictory message of the Qur'an. This study concludes that mastering the concepts of 'Amm and Khash is crucial for mufassir and fuqaha (jurists) to avoid arbitrary and extreme interpretations and to produce legal conclusions that are contextual, comprehensive, and relevant to the dynamics of the times. Their proper application ensures the elasticity and continuity of Islamic law in addressing contemporary issues.